Leading Indicators of Banking Crises : Was Asia Different? (IMF Working Papers; Working Paper ;, 1998)
This paper examines episodes of the banking system distress and crisis in a large sample of countries. The empirical results identify several macroeconomic and financial variables as useful leading indicators. The main macroeconomic indicators were of limited value in predicting the Asian crises; the best warning signs were proxies for the vulnerability of the banking and corporate sector. Full-blown banking crises are shown to be more associated with external developments, and domestic variables are the main leading indicators of severe but contained banking distress.